Pulling force characteristics of 10s maximal tethered eggbeater kick in elite water polo players - Dopsaj, M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: In water polo, duel play is the players` basic technical and tactical (TE-TA) position in both offense and defense. The position essentially enables players to block the opponent by holding their arms so as to perform the TE-TA elements, using the eggbeater kick technique simultaneously. This paper aimed to define the basic kinematical and mechanical characteristics of 10s maximal tethered eggbeater kicks in elite water polo (WP) players. METHODS: The study involved 14 male elite WP players (Age=21.5±5.1yrs, BH=187.2±6.1cm, BM=84.5±11.9kg, training experience=11.7±3.6yrs). The tests were conducted in the middle of the national premiere league preparation period for the 2006/07 competition season. A standard procedure was used, applying the tethered puling force methods, and the players had to realize the maximal pull force of 10s duration only by eggbeater kicks while in the chest-forward position. The following measurements of the kinematical and mechanical characteristics of pulling force were taken: the duration of a single eggbeater kick (TimeEBK), in ms; the maximal (peak) force value realized by a single eggbeater kick (FmaxEBK), in N; the average force value realized by a single eggbeater kick (FavgEBK), in N; the impulse of force (ImpFEBK), in Ns; the single eggbeater kick explosive force (RFDEBK), in N/s; and the single eggbeater kick frequency (HzEBK), expressed in the numbers of kicks per minute. All data were treated in absolute and relative values with the descriptive statistical method. RESULTS: The descriptive variable results yielded the following absolute values: TimeEBK=497.78±56.95 ms; FmaxEBK=190.52±36.04; FavgEBK=140.44±21.12; Imp-FEBK=72.95±14.32; RFDEBK=336.73±98.89; HzEBK=120.08±14.70 Kicks/min. The descriptive variable results yielded the following relative values: FrelEBK=2.295±0.534 N-kgBW; FavgrelEBK=1.689±0.327 N-kgBW; ImpFrelEBK=0.880±0.214 Ns-kgBW; RFDrelEBK= 4.105±1.610 N/s-kgBW. DISCUSSION: The results indicated the descriptive values of the kinematical and mechanical characteristics of the 10s maximal tethered eggbeater kick in elite water polo players with regard to the absolute and relative values. Also, the resulting models could help towards the development of the water polo training technology, as well as the establishment of a new method to test the specific leg fitness in elite senior water polo player.